Implementing a treated wastewater recharge technique and reverse osmosis unit system for water sustainability - AlAli, Emad Hussain, author; Warner, James W., advisor; Smith, Freeman, committee member; Oad, Ramchand, committee member; Namvargolian, Reza, committee member (Colorado State University. Libraries, 2004)
The aim of this dissertation was to design a conceptual system to provide a sustainable water source at a feasible cost. The conceptual design system was developed to address the problem of water scarcity and sustainability in general, and specifically to represent the Kuwaiti water quality and quantity limitation problem. The conceptual design system consists primarily of utilizing brackish groundwater in conjunction with treated wastewater augmentation and a reverse osmosis unit. The dissertation considered two types of simulation models for the conceptual design system approach. These models are the lump model approach and the areal distribution model approach. The lump model approach was carried out through the construction of a simplified model approach utilizing the Visual Basic model. On the other hand, the areal distribution model approach was carried out through the utilization of the Visual MODFLOW and MT3D simulation model approach. To test the sensitivity and the durability of the conceptual design system, the lump model simulation approach was simulated for different ranges of hydrologic, hydrogeologic, and climatic parameters to determine the total power and treated wastewater consumption. Moreover, to valuate the robustness of the general conceptual design system by performing different operational scenarios, four perturbed scenarios of the general conceptual design system utilizing the lump model approach were performed and compared with the base case simulation of the general conceptual design system utilizing a lump model approach. The base case simulation was chosen to represent the quasi-Kuwaiti environment data. In addition, the areal distribution model simulation approach of the general conceptual model design was simulated for three orientation layouts and compared to the lump model simulation approach of the general conceptual design system to determine the total cost of operating the system. The economical feasibility of the base case of the general conception design system was analyzed for the lump model simulation approach and for the three orientation layouts of the areal distribution model approach. The economical analysis was based on the calculations of the net present worth value of the cash flows for the capital cost, the operation and maintenance costs, and the revenues of the crop yields for the 40 years of operation. The benefit-cost ratios for the base case of the general conceptual design system using the lump model approach and the areal distribution model for the three orientation layouts were calculated for ranges of different interest rates. The benefit-cost ratios were feasible for the Middle East condition in general and to the GCC countries in particular, especially at low interest rates.
Keywords: civil engineering; hydrology; environmental engineering; sanitation